Beyond the Posts: Understanding Student Discourse on Social Media through Content Analysis - Ndukwani, Tiyiselani (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2024)
This paper explores students' use of social media platforms, primarily focusing on Facebook, Twitter, and WhatsApp. Understanding the intricacies of student discourse can inform strategies to enhance digital literacy, foster constructive conversations, and create supportive online environments for academic and personal development. The findings of this study contribute valuable insights into the complex world of student discourse on social media, offering a deeper understanding of the dynamics that influence online interactions. This investigation aimed to understand how students use these platforms, examining engagement patterns and purposes. To achieve this, the researcher employed a qualitative method research approach. The researcher purposefully sampled 90 students from the University of Technology (UoT) in Gauteng, South Africa, to collect data. The participants submitted extracts from Facebook, WhatsApp, and Twitter texts for analysis. Findings revealed that students could benefit from using Facebook, WhatsApp, and Twitter for educational purposes since the document analysis indicated education as a prominent topic discussed on all the platforms. Another salient topic that emerged from the data was the topic of social discourse linked with love and relationships.